Automophism of unitary groups of B(H) and Norm-attainable elementary operators - Achieng, Otieno Esther (JOOUST PhD Student, 2015)
The study aim at exploring various applications in quantum physics, specifically, commutator approximation, the ground state energy of the chemical systems and sub-systems and food processing techniques
Students' project